Microplate assay for quantitative determination of cathepsin activities in viable cells using derivatives of 4-methoxy-beta-naphthylamide - Rüttger, Anke (BioTechniques, 2006)
A method is described allowing the selective determination of four cathepsins (B, H, K, and L) in live cells. Adherently growing cells are incubated with partially selective substrates for each cathepsin (peptidic derivatives of 4-methoxy-beta-naphthylamine) in microtiter plates together with nitrosalicylaldehyde. Using an appropriate reader accumulating fluorescent products may be detected continously or by end point measurement. Selectivity is achieved by running parallel assays containing inhibitors that are partially selective for each of the cathepsins (in case of cathepsin H, the nonlysosomal aminopeptidases are inhibited by bestatin). Individual cathepsin activities can then be calculated by the difference between the uninhibited and the inhibited assay. The method was validated by measurements in cells isolated from cathepsin B(-/-)-, K(-/-)-, and L(-/-)- mice. This strategy suggests that the combination of two partially selective reaction partners, substrate and inhibitor can yield selective cathepsin assays